2021
DOI: 10.1038/s41598-021-03624-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural analysis of non-synonymous single nucleotide polymorphisms (nsSNPs) in the MYB oncoproteins associated with human cancer

Abstract: MYB proteins are highly conserved DNA-binding domains (DBD) and mutations in MYB oncoproteins have been reported to cause aberrant and augmented cancer progression. Identification of MYB molecular biomarkers predictive of cancer progression can be used for improving cancer management. To address this, a biomarker discovery pipeline was employed in investigating deleterious non-synonymous single nucleotide polymorphisms (nsSNPs) in predicting damaging and potential alterations on the properties of proteins. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The average DDG was -0.73 kcal/mol. According to reference criteria, DDG < -0.5, indicating large decrease of protein structure stability ( Lim et al, 2021 ). In our article, ARG 215 was hydrogen binding location, results of mutation revealing the important function of this location.…”
Section: Resultsmentioning
confidence: 99%
“…The average DDG was -0.73 kcal/mol. According to reference criteria, DDG < -0.5, indicating large decrease of protein structure stability ( Lim et al, 2021 ). In our article, ARG 215 was hydrogen binding location, results of mutation revealing the important function of this location.…”
Section: Resultsmentioning
confidence: 99%
“…Fundamentally, functions of a protein are defined and confined by the protein primary structure (i.e., amino acid sequence) that determines its three-dimensional structure . However, a nsSNP may impair the structure and functions of a protein; for instance, Lim et al (2021) observed alteration of the DNA-binding specificities of MYB family proteins due to nsSNPs and PTMs . The results obtained from the SNP search and analyses revealed two important nsSNPs, namely, F66L and E92K, and both were predicted as a pathogenic substitution (Table ).…”
Section: Discussionmentioning
confidence: 99%
“… 32 However, a nsSNP may impair the structure and functions of a protein; for instance, Lim et al (2021) observed alteration of the DNA-binding specificities of MYB family proteins due to nsSNPs and PTMs. 33 The results obtained from the SNP search and analyses revealed two important nsSNPs, namely, F66L and E92K, and both were predicted as a pathogenic substitution ( Table 2 ). Protein’s stability is an indicator of how well a protein keeps a particular shape.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the nsSNPs of FGF4 were subjected to different bioinformatics tools to determine their structural and functional effect on the protein [ 30 ]. Damaging nsSNPs were predicted using five different tools, resulting in 27 nsSNPs as “highly damaging”.…”
Section: Discussionmentioning
confidence: 99%